Comparison of Efficacy of Metformin and Insulin in management of Gestational Diabetes. An experience in Social Security Teaching Hospital, Ferozepur Road Lahore - Asma Sarwat, Najma Perveen, Amina Saleem, Faisal Rehman, Iqra Zafar, Ghazala Iftikhar (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the feto-maternal outcomes in patients receiving metformin with those receiving standard insulin therapy for management of gestational diabetes mellitus (GDM). Methods: This randomized control study was conducted in gynecology unit of Social security Teaching Hospital, Ferozepur Road Lahore from January-2021 to December-2021. We included patients of GDM who needed pharmacologic intervention. In group M; Metformin was administered at a dose of 500mg twice daily for the first week, followed by an increase to a maximum dose of 2500mg daily in divided doses until the goal glycemic control was reached. In group I patients, regular insulin (Humulin R) was prescribed three times a day before each meal, with a single dose of intermediate acting insulin (NPH) given at bedtime. The primary study outcomes were birth weight, APGAR score, pre-term birth and maternal HBA1c levels before birth. Results: Maternal HbA1c levels before birth were 6.1±1.1 in group M and 6.0±1.2 in group I (p-value 0.66). The mean gestational age at birth was 37.9±1.1 weeks in group M and was 37.1±1.0 weeks in group I (p-value 0.0002). The frequency of pre-term was high in group I (16%) in comparison to only 6.0% in group M, but with insignificant p-value 0.11. The mean birth weight was 2.9±0.5 Kg in group M and 3.0±0.6 kg in group I (p-value 0.36). Conclusion: Better maternal glycemic control has been linked to the usage of metformin during pregnancy. In terms of patient compliance, the medicine is well tolerated. Patients with gestational diabetes mellitus who took Metformin experienced fewer neonatal problems than those who used insulin.